The erection of a new genus, Neotegorhynchus n. g. (Palaeacanthocephala, Illiosentidae), with a redescription of Neotegorhynchus cyprini n. comb. from Cyprinus carpio from the Yangtze River basin, China - Lisitsyna, Olga; Xi, Bing-Wen; Orosová, Martina; Barčák, Daniel; Oros, Mikuláš (Zootaxa, 2022)
The present paper summarizes acanthocephalan parasites of the family Illiosentidae Golvan, 1960, collected from the intestine of common carp (Cyprinus carpio L.) from Taihu Lake in Wuxi, Jiangsu Province, China. A total of 21 acanthocephalan specimens were found in 6 carps (prevalence of 35%). All the studied specimens were assigned to the family Illiosentidae based on the family-specific morphology of the worms and the presence of 8 cement glands in the males. However, the specimens recently found in common carp differed from all 14 extant genera of the family Illiosentidae in the structure of the reproductive system of both sexes, i.e. i) a vagina lacking a muscular sphincter; ii) the presence of a terminally pointed protruding tail end in the form of a dome with a muscular base; iii) the female genital muscles are fan-shaped cells, each of which has a nucleus and is not attached to the anterior wall of the body; iv) the muscular lip of the bursa of males repeats the curved shape of the posterior end of females, which en copula allows the lip of the bursa to seal to the posterior end of the female. Morphologically Neotegorhynchus n. g. is closest to the genus Tegorhynchus, but differs from it, in addition above features in i) the terminal position of the genital pores of females without a hollow genital vestibule and without a transverse cleft connected to the dorsal terminal genital pore, as in Tegorhynchus brevis; ii) cerebral ganglion at the border of the anterior and middle third of the proboscis vessel; iii) spherical cement reservoir. Molecular studies confirmed Neotegorhynchus n. g. as belonging to the family Illiosentidae, showing less than 98.9% sequence similarity in SSU rDNA and 81.8% in COI with the genus Dentitruncus. Therefore, a new acanthocephalan genus, Neotegorhynchus n. g., is erected, and Neotegorhynchus cyprini n. comb. is designated as the type species and its neotype.